The Causes and Consequences of Childhood Encephalitis in Asia - N. Britton, Philip; Khandaker, Gulam; Booy, Robert; A. Jones, Cheryl (Infectious Disorders - Drug Targets, 2014)
Encephalitis is caused by inflammation and/or infection of the brain. It is a important condition in Asian children in whom it is most frequently caused by Japanese encephalitis virus, associated with a considerable burden of disease. Other common causes in Asia include: enteroviruses (especially enterovirus 71), dengue, influenza, the herpesviruses, measles, mumps and rubella viruses. Rabies continues to result in high mortality mostly in Asian children, which represents missed opportunities for prevention. Asia has also seen a number of emerging viral encephalitides including: Nipah, chikungunya, Chandipura and Me Tri viruses. We review the aetiology, epidemiology and outcome of encephalitis in Asian children and identify priorities for public health practice and research.
Keywords: children